(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
This article examines the current condition of agricultural lands and identifies prospects for their sustainable and productive utilization under conditions of climate change, water scarcity, and increasing land degradation. The study focuses on the geomorphological, agro-reclamation, and ecological status of agricultural land resources, with particular attention to secondary salinization, waterlogging, erosion, declining soil fertility, and reduced biomass productivity. A comprehensive methodological approach was applied, including systems analysis, comparative geographical assessment, laboratory investigations, mathematical-statistical methods, and geospatial analysis. Multispectral data from Landsat-8 and Sentinel-2 satellites were processed using GIS and remote sensing technologies, while NDVI indicators were used to evaluate vegetation condition and land productivity. The results show that 28–32% of agricultural areas are affected by soil degradation, while secondary salinization has intensified in nearly 35% of irrigated lands. Laboratory findings also revealed a 10–15% decline in soil quality scores. At the same time, areas where laser land leveling, drip irrigation, and sprinkler irrigation were introduced demonstrated reduced water consumption, lower erosion risk, and increased crop yields. The article concludes that sustainable land management requires the integration of traditional agricultural practices with GIS, remote sensing, and resource-efficient irrigation technologies.